Rotten from all that came before? How interest convergence has informed and usurped initiatives for racial progress in the UK - Klots, Jens; Ogwude, Uche (Frontiers in Education, 2025)
This discussion paper examines how British Higher Education Institutions (HEIs) approach anti-racist and decolonial initiatives through the lens of Interest Convergence (IC). It highlights how institutional actions, largely sparked by the Black Lives Matter (BLM) protests in 2020, align with existing neoliberal and capitalist priorities—therefore limiting their transformative potential. While efforts to participate in the Race Equality Charter (REC) and decolonise the curriculum have gained traction, they are often implemented in ways that fail to properly address systemic inequalities. Finally, a case is made for ritual theory as a potential vehicle to educate staff and students about IC, as ritualised activities can promote community building and wider cultural change.